The mechanics of democracy promotion tools: bridging the knowledge-to-practice gap. Issue 4 (18th May 2016) - Alihodžić, Sead
ABSTRACT: By drawing upon the literature that diagnoses the gap between academics and practitioners, this article categorises and describes the traditional democracy promotion tools developed by international governmental and non-governmental organisations to bridge the gap between knowledge and practice. Further, it examines the utility of ICTs in promoting and upholding democratic change. The findings inform considerations and specific recommendations offered to the tool developers on how to converge traditional and new democracy promotion tools. These are intended to assist in focusing tool design and development efforts, and promoting standardisation and innovation.